90 years anniversary of the Pathophysiology Chair with the Clinical Pathophysiology Course of the Omsk State Medical Academy - V. T. Dolgikh; N. I. Taran; A. N. Zolotov (Бюллетень сибирской медицины, 2012)
Chair of Pathologic Physiology with Clinical Pathophysiology Course of the OmskStateMedicalAcademyhas celebrated its 90th anniversary with the latest achievements in the pathogenesis of postresuscitation disease. Experimental resuscitation model exploited by the staff of the Chair is allowed to extend knowledge in respect to the nature of hemodynamic disorders, endogenous toxemias, functional and metabolic aspects of hypoxia and reoxygenation in terminal and critical states including other significant problems of the pathology. The Chair of Pathologic Physiology is going on with the scientific inquiries in close collaboration with the Clinical Chair of the Academy and Research Units of Russia.